Cross-sectional exploratory survey among health researchers in Europe on the awareness of and barriers affecting the use of an evidence-based research approach - Tella Lantta; Hans Lund; Malgorzata M Bala; Tina Poklepović Peričić; Joanna Zając; Sabine Van Eerdenbrugh; Luca Pingani; Tamara Prevendar; Anna Prokop-Dorner; Maria Piedade Brandão; Joost van Hoof (BMJ Open)
Objectives This exploratory study was conducted to find out how well the concept of evidence-based research (EBR) is known among European health researchers with substantial clinical research experience, and which barriers affect the use of an EBR approach. The concept of EBR implies that researchers use evidence synthesis to justify new studies and to inform their design.Design A cross-sectional exploratory survey study.Setting and participants The survey was conducted among European health researchers. Respondents included 205 health researchers (physicians, nurses, dentists, allied health researchers and members of other professions involved in health research) with a doctoral degree or at least 5 years of research experience.Primary and secondary outcome measures The primary outcome measures were the level of awareness of the concept of EBR and the presence of barriers affecting the use of an EBR approach. Secondary outcome measures include correlations between sociodemographic characteristics (eg, profession) and awareness of EBR.Results We discovered that 84.4% of the respondents initially indicated their awareness of the concept of EBR. Nevertheless, 22.5% of them concluded that, on reading the definition, they either do not know or do not fully comprehend the concept of EBR. The main barriers affecting the use of an EBR approach were related to organisational issues, such as not being attributed resources (30.5% of the respondents), time (24.8%) or access to implement it (14.9%).Conclusions Despite the limitations, this study clearly shows that ongoing initiatives are necessary to raise awareness about the importance of implementing the EBR approach in health research. This paper contributes to a discussion of the issues that obstruct the implementation of the EBR approach and potential solutions to overcome these issues, such as improving the knowledge and skills necessary to practice the EBR approach.